Disruptions of neurological services, its causes and mitigation strategies during COVID-19: a global review - García-Azorín, D; Seeher, KM; Newton, CR; Okubadejo, NU; Pilotto, A; Saylor, D; Winkler, AS; Charfi Triki, C; Leonardi, M (Springer, 2021)
Background The COVID-19 pandemic leads to disruptions of health services worldwide. To evaluate the particular impact on neurological services a rapid review was conducted. Methods Studies reporting the provision of neurological services during the pandemic and/or adopted mitigation strategies were included in this review. PubMed and World Health Organization’s (WHO) COVID-19 database were searched. Data extraction followed categories used by WHO COVID-19 pulse surveys and operational guidelines on maintaining essential health services during COVID-19. Findings The search yielded 1101 articles, of which 369 fulfilled eligibility criteria, describing data from 210,419 participants, being adults (81%), children (11.4%) or both (7.3%). Included articles reported data from 105 countries and territories covering all WHO regions and World Bank income levels (low income: 1.9%, lower middle: 24.7%, upper middle: 29.5% and high income; 44.8%). Cross-sectoral services for neurological disorders were most frequently disrupted (62.9%), followed by emergency/acute care (47.1%). The degree of disruption was at least moderate for 75% of studies. Travel restrictions due to lockdowns (81.7%) and regulatory closure of services (65.4%) were the most commonly reported causes of disruption. Authors most frequently described telemedicine (82.1%) and novel dispensing approaches for medicines (51.8%) as mitigation strategies. Evidence for the effectiveness of these measures is largely missing. Interpretation The COVID-19 pandemic affects all aspects of neurological care. Given the worldwide prevalence of neurological disorders and the potential long-term neurological consequences of COVID-19, service disruptions are devastating. Different strategies such as telemedicine might mitigate the negative effects of the pandemic, but their efficacy and acceptability remain to be seen.